Valuing the Impact of A Mega Project on Indigenous Peoples The case of Ibu Kota Nusantara (IKN) - Annisa,Aninda (IIIEE Master Thesis, 2025)
Indonesia is in the process of relocating its capital to a newly built city named Ibu Kota Nusantara (IKN). The first area to be developed is the central area of IKN (KIKN), which includes the main governmental zone (KIPP) and is located in Penajam Paser Utara (PPU), spanning two primary villages, Sepaku and Pemaluan, which are home to the Indigenous Peoples (IP) of the Balik and Paser communities. Research has shown that the IP are affected by the IKN development, forcing them to be displaced, which leads to the loss of economic opportunities from farming, loss of ritual access and maintaining ancestral connections, and loss of homes or buildings, where all these aspects are linked to one: Indigenous Land. However, despite the extensive research identifying the implications of IKN projects for the IP, no one has estimated the economic value of such impact, which may allow it to serve as an input in determining costs or benefits in future decisions related to the project. This thesis aims to estimate the economic value of three key impacts of IKN on the IP tied to the loss of indigenous land as IKN projects acquire and alter the land. The study employs the contingent valuation method (CV) to estimate the value of the loss of ritual access and maintaining ancestral connections, as these are considered non-market goods. Market-based valuations are also utilised to estimate the value of lost farming and housing land since the outputs of these activities are traded in the market. The results of the CV are analysed using both parametric and non-parametric estimation techniques, where probit and biprobit models are also employed, given that the CV study uses a double-bounded dichotomous model. For the market-based method, an annual income calculation is developed to estimate the relevant losses of the IP. The results show that the IP, as a community, are significantly undercompensated by the IKN project and suggest that the development of IKN should consider the rights of the IP for a just and sustainable development, as the city aimed.
Keywords: IKN; Economic Valuation; Indigenous Peoples; Mega Project.